2020
DOI: 10.1098/rsos.191700
|View full text |Cite
|
Sign up to set email alerts
|

Different laterality indexes are poorly correlated with one another but consistently show the tendency of males and females to be more left- and right-lateralized, respectively

Abstract: The most common way to assess handedness is based on the preferred hand for writing, leading to a binary (left or right) trait. Handedness can also be assessed as a continuous trait with laterality indexes, but these are not time- and cost-effective, and are not routinely collected. Rarely, different handedness measures are collected for the same individuals. Here, we assessed the relationship of preferred hand for writing with four laterality indexes, reported in previous literature, derived from measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Most of the studies included in our metaanalysis only provided information on hand preference, not allowing for an additional analysis for hand skill. Moreover, hand preference and hand skill correlate to some extent (Buenaventura Castillo, Lynch, & Paracchini, 2020;Todor & Doane, 1977;Triggs, Calvanio, Levine, Heaton, & Heilman, 2000), and the distribution of handedness categories overlaps for preference-and skill-related criterions in 90 % of the cases (Corey, Hurley, & Foundas, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies included in our metaanalysis only provided information on hand preference, not allowing for an additional analysis for hand skill. Moreover, hand preference and hand skill correlate to some extent (Buenaventura Castillo, Lynch, & Paracchini, 2020;Todor & Doane, 1977;Triggs, Calvanio, Levine, Heaton, & Heilman, 2000), and the distribution of handedness categories overlaps for preference-and skill-related criterions in 90 % of the cases (Corey, Hurley, & Foundas, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the pegboard task as a measure of hand skill was not sensitive enough to capture the handedness effect. Indeed, different measures of hand skill have been found to have low correlation with each other (0.08-0.3), suggesting that they tap into different dimensions of laterality and that they cannot be used interchangeably (Buenaventura Castillo, Lynch, & Paracchini, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants of the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort [19] were assessed with hand preference at different time points, handedness questionnaires, and multiple motor tasks, which can be used to derive LQ (N up to 8000). Thanks to these data, we showed that different laterality measures are poorly correlated with one another [20] and, beyond capturing a general left/right component, they tap in different laterality dimensions. Moderate correlation (0.42) for handedness measures derived from the EHI and the pegboard task was also reported in 205 twin pairs recruited in Hong Kong.…”
Section: How To Measure Handednessmentioning
confidence: 91%